Early- Mid Pleistocene environments in the Valsequillo Basin, Central Mexico: a reassessment - Metcalfe, Sarah E.; Leng, Melanie J.; Kirby, Jason R.; Huddart, David; Vane, Christopher H.; Gonzalez, Silvia (Wiley-Blackwell, 2016)
The Valsequillo Basin in Central Mexico has been of interest due to the presence of megafauna and evidence for early human occupation, but research has been controversial. It has been suggested that extensive and deep lakes characterised the Early Pleistocene environment but sediment exposure is highly fragmentary and reliable dating has been difficult. Here we report, for the first time, Early Pleistocene palaeoenvironmental reconstructions using stable isotopes,diatoms, tephra and pollen. We studied several stratigraphic sections of mainly non-volcanic rocks, containing the 1.3 Ma Xalnene Ash as a stratigraphic marker. The isotope and other proxy data show that topographically low points in the basin were occupied by spring-fed, shallow water lakes during the Early – Mid Pleistocene, with a trend to drier conditions. The basin was a dynamic volcaniclastic environment during this period, with the production of the Toluquilla Volcano sequence and other rhyolitic-dacitic volcanic ashes interbedded with the lake sediments at the sections studied. There is no evidence from the sections for extensive and deep lakes before or after the Xalnene ash deposition. The presence of lakes in the basin during the Early Pleistocene would have made it attractive for megafauna.